SPECTRAL DOMAIN OPTICAL COHERENCE TOMOGRAPHIC ANALYSIS OF HEALTHY RETINA IN BRANCH RETINAL VEIN OCCLUSION AND ITS RESPONSE TO ANTIANGIOGENIC THERAPY. Issue 4 (April 2015) - Salcedo-Villanueva, Guillermo; Harasawa, Mariana; Velez-Montoya, Raul; Mathias, Marc T.; Siringo, Frank S.; Olson, Jeffrey L.; Oliver, Scott C.; Mandava, Naresh; Quiroz-Mercado, Hugo
Abstract : Purpose: To propose a model that measures the effect of intravitreal bevacizumab (IVB) on relatively healthy retina. The purpose is to analyze the remote effect of a branch retinal vein occlusion in the healthy retina, to determine the response it may have to IVB, and to determine if IVB has an atrophic effect on the healthy retina. Methods: Retrospective, longitudinal comparative analysis of patients with branch retinal vein occlusion treated with IVB. Eyes were divided into experimental (branch retinal vein occlusion eye) and control (contralateral eye) groups. Each eye was analyzed for thickness and area. Thickness measurements were performed for total retinal thickness, inner retina thickness, and outer retina thickness. Area was measured for photoreceptors, choroid, and total retina. Results: Eighteen eyes of 9 patients. For thickness analysis, 1, 050 scans were studied, and 126 measurements were performed on 42 scans for area analysis. No difference was observed for thickness, except for inner retina thickness. No difference was observed for area. No difference was observed when analyzing a cumulative exposure to IVB. Conclusion: There is no evidence to suggest an atrophic effect caused by IVB when analyzing thickness or area in this experiment. This model could be used to analyze the long-term safety of IVB in larger studies. Abstract : To propose a model that determines potential toxicity in the healthy retina from exposure to intravitreal bevacizumab in patients with branch retinal vein occlusion.